ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT DAN KEPUTUSAN SISWA SMA SEDERAJAT DI KABUPATEN ROKAN HILIR DALAM MEMILIH PROGRAM STUDI DI PERGURUAN TINGGI - Ahmat Hidayat; Zulkarnain '; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of Factors Influencing High School Students Interest and Decision in Rokan Hilir in Choosing Studies Program in Higher Education. This study used 99 samples. The analytical method used is descriptive analysis method is by means of a variable test, regression test, and final analysis test track or path analysis. From the results of the testing that has been done, there is a significant effect of both partially and simultaneously between economic status, course of study, situational, psychological state of the interest rate of high school students Rokan Hilir in courses at Universities and the psychic state of the factors is the most influential factor significantly to the high school level students decision Rokan Hilir in choosing a course of study at university.Keywords: Economic status, course of study, situational, psychological state, interests of students, student decision